Pengaruh Dukungan Sosial, Keterlibatan Karyawan, dan Work Life Balance terhadap Kepuasan Kerja Karyawan PT. Dian Indah Logam Cabang Palembang - Safitriana, Ririn; Hamid Halin; Siti Komariah Hildayanti (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
This study aims to analyze the impact of social support, employee engagement, and work life balance both partially and simultaneously on the job satisfaction of employees of PT Dian Indah Logam Palembang branch. This type of research is quantitative descriptive. The total employee population at PT Dian Indah Logam Palembang branch is 80 respondents. The technique for determining the number of samples uses saturated sampling. Data analysis used data quality tests, classical assumption tests, and multiple linear regression analysis with t-test (partial), F test (simultaneous), and R-test. Employee engagement has a positive and significant effect on employee job satisfaction. Work-life balance has a positive and significant effect on employee job satisfaction. Social support, employee engagement, and work-life balance have a positive and significant effect on employee job satisfaction at PT Dian Indah Logam Palembang branch.